Konsep Kepemilikan Tanah Adat Suku Tolaki Mekongga Serta Hak Atas Tanah Ulayatnya - Yahyanto Yahyanto; Riezka Eka Mayasari; Irabiah Irabiah; Nur Hidayani Alimuddin; Jusafri Jusafri (Jurnal Multidisiplin Dehasen (MUDE), 2023)
Ulayat rights are the rights of customary law communities which in essence are the authority possessed by certain customary law communities. The customary land law of the Tolaki Mekongga tribe is land that is controlled or owned by a family, either because the family has directly cultivated it, or because the land has been inherited from generation to generation. The main objective of this research is to find out the concept of customary land ownership of the Tolaki Mekongga tribe and its relation to inheritance and customary rights. The type of research used in this study is normative legal research (doctrinal legal research), namely research on law as a norm and reality (behavior) or as something to aspire to and as a living reality or law. The Tolaki Mekongga indigenous people still exist today and occupy certain areas, but until now there are no regional regulations regarding customary rights over these areas, so efforts are needed to obtain legal certainty and justice for customary law communities in managing their customary rights.